An exploratory study of the management strategies reported by endurance athletes with exercise-associated gastrointestinal symptoms - Scrivin, Rachel; Costa, Ricardo J. S.; Pelly, Fiona; Lis, Dana; Slater, Gary (Frontiers in Nutrition, 2022)
This exploratory study investigated endurance athletes self-reported exercise-associated gastrointestinal symptoms (Ex-GIS) and associated strategies to manage symptomology. Adult endurance athletes with a history of Ex-GIS (n =137) participating in events ≥60 minutes completed an online validated questionnaire. Respondents included runners (55%, n = 75), triathletes (22%, n = 30), and non-running sports (23%, n = 32), participating at a recreationally competitive (37%, n = 51), recreationally non-competitive (32%, n = 44), and competitive regional/ national/ international (31%, n = 42) levels. Athletes identified when Ex-GIS developed most frequently either around training (AT), around competitions (AC) or equally around both training (ET) and competitions (EC). Athletes reported the severity of each symptom before, during and after exercise. Athletes predominantly categorized Ex-GIS severity as mild (< 5/10) on a 0 (no symptoms) to 10 (extremely severe symptoms) visual analogue symptomology scale. The Friedman test and post-hoc analysis with Wilcoxon signed rank test was conducted with a Bonferroni correction applied to determine differences between repeated measures. The only severe symptom of significance was the urge to defecate during training in the ET group (Z = -.536, p = 0.01). Ex-GIS incidence was significantly higher during training and competitions in all categories. A content review of self-reported strategies (n = 277) to reduce Ex-GIS indicated popular dietary strategies were dietary fiber reduction (15.2%, n = 42), dairy avoidance (5.8%, n = 16), and a low fermentable oligosaccharides, monosaccharides, and polyols (FODMAP) diet (5.4%, n = 15). In contrast, non-dietary strategies included the use of medications (4.7%, n = 13) and relaxation/ meditation (4.0%, n = 11). On a Likert scale of 1 to 5, the most successful dietary strategies implemented were dietary fiber reduction (median = 4, IQR = 4, 5), low FODMAP (median = 4, IQR = 4, 5), dairy-free (median = 4, IQR = 4, 5) and increasing carbohydrates (median = 4, IQR = 3, 4). Accredited practicing dietitians were rated as the most important sources of information for Ex-GIS management (n = 29). Endurance athletes use a variety of strategies to manage their Ex-GIS, with dietary manipulation being the most common.